2020
DOI: 10.1177/0003702820923993
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Hybrid Fusion Classification Process for Identification of Microplastics Based on Fourier Transform Infrared Spectroscopy

Abstract: Microplastic research is an emerging field. Consistent accurate identification of microplastic polymer composition is vital for understanding the effect of microplastic pollution in the environment. Fourier transform infrared (FT-IR) spectroscopy is becoming commonplace for identifying microplastics. Conventional spectral identification is based on library searching, a process that utilizes a search algorithm against digital databases containing single spectra of pristine reference plastics. Several conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 67 publications
1
39
0
Order By: Relevance
“…Rios-Fuster et al, 2019;Savoca et al, 2019). Here we confirmed that both our target species ingest plastic materials that range in size from 250 to 3000 μm and are represented by polypropylene, high density polyethylene and polyamide items (Chabuka and Kalivas, 2020;Primpke et al, 2018). Benthic macrolitter in the area was recently described quali-quantitatively, and the most abundant categories were attributed to plastic (Mancini et al, 2021).…”
Section: Discussionsupporting
confidence: 84%
“…Rios-Fuster et al, 2019;Savoca et al, 2019). Here we confirmed that both our target species ingest plastic materials that range in size from 250 to 3000 μm and are represented by polypropylene, high density polyethylene and polyamide items (Chabuka and Kalivas, 2020;Primpke et al, 2018). Benthic macrolitter in the area was recently described quali-quantitatively, and the most abundant categories were attributed to plastic (Mancini et al, 2021).…”
Section: Discussionsupporting
confidence: 84%
“…Cross-reference of spectra retrieved from the ATR-FTIR instrument was performed with the open source database Open Specy (www.openspecy.org; Cowger et al, 2021). The Open Specy tool includes 636 spectra of 276 materials from three libraries of pure polymers, and materials relevant to microparticles and fibers found in the environment (Primpke et al, 2018;Chabuka and Kalivas, 2020;Suja Sukumaran, Thermo Fisher Scientific).…”
Section: Ft-ir Analysismentioning
confidence: 99%
“…Moreover, training the classifier can increase the analysis speed substantially when dealing with large datasets of FTIR spectra. For example, automated identification methods were tested based on hierarchical cluster analysis (Primpke et al, 2018), shortwave infrared imaging (Schmidt et al, 2018), identification of the most relevant bands (Renner et al, 2017;Renner, Nellessen, et al, 2019), random decision forest method (Hufnagl et al, 2019), modified chemometric identification concept (Renner, Sauerbier, et al, 2019), machine learning method (Kedzierski et al, 2019), Python based lFTIR mapping (Renner et al, 2020) and Hybrid fusion method (Chabuka & Kalivas, 2020). The analysis of FTIR spectra is time-consuming as often it is needed to compare the spectra one by one with the reference spectra.…”
Section: Analytical Methods and Future Challengesmentioning
confidence: 99%